Fast fixes for common PC problems. - Broida, Rick
Struggling with dead components, a recalcitrant Windows, and uncooperative applications? Our easy hardware repairs, simple software remedies, and quick tweaks will put your PC in the pink.
Keywords: Personal computers--repairs.